Synthesis and Biological Evaluation of Methylenecyclopropane Analogues of Nucleosides - Obame, Germain; Brémond, Paul; Pannecouque, Christophe; Audran, Gérard (Synthesis, 2013)
Starting from a chiral methylenecyclopropane building block, readily obtained by enzymatic desymmetrization of a meso-diol, two types of methylenecyclopropane analogues of nucleosides were synthesized. The first type of nucleosides was obtained from the direct coupling of the chiral building block with 6-chloropurine under Mitsunobu reaction conditions followed by the functionalization of the purine base. The second type of nucleosides featured a Curtius rearrangement as the key step and the uracil heterocycle was then constructed by a linear methodology. These derivatives were evaluated as potential agents against important viral pathogens. None of the new compounds had significant antiviral activity at a concentration of 100 μg/mL, which was the highest concentration tested.
Keywords: stereoselective synthesis; Curtius rearrangement; carbocyclic nucleosides; methylenecyclopropane carbonucleosides; antiviral agents